2003
DOI: 10.1046/j.1095-8312.2003.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant clonality, mutation, diplontic selection and mutational meltdown

Abstract: Apomixis is a very common characteristic in vascular plants. It occurs in two general forms: either subversion of the sexual system (agamospermous seeds or apogamous sporophytes in non‐seed plants) or vegetative reproduction. In this communication, only the mutational consequences of vegetative reproduction are considered. Vegetative reproduction involves the replication of apical meristems, especially shoot apical meristems. Three general types of shoot apical meristems occur in the vascular plants: single te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 38 publications
4
87
0
Order By: Relevance
“…Somatic mutations result in minor DNA variation within clonal lineages (James & McDougall 2014) and it is suggested that old clones may accumulate somatic mutations to a greater extent (Wyman et al 2003, Tuskan et al 2006, Mock et al 2008. Understanding the development of somaclonal variation requires closer attention because older and slowly-growing clones could have levels of mutations similar to those of younger, faster-growing clones, as the mutation rate is expected to be proportional to the number of mitotic divisions (Klekowski 2003, Ally et al 2008, James & McDougall 2014. As somatic mutations accumulate in clones, the remaining stems may appear to be genetically distinct clones.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic mutations result in minor DNA variation within clonal lineages (James & McDougall 2014) and it is suggested that old clones may accumulate somatic mutations to a greater extent (Wyman et al 2003, Tuskan et al 2006, Mock et al 2008. Understanding the development of somaclonal variation requires closer attention because older and slowly-growing clones could have levels of mutations similar to those of younger, faster-growing clones, as the mutation rate is expected to be proportional to the number of mitotic divisions (Klekowski 2003, Ally et al 2008, James & McDougall 2014. As somatic mutations accumulate in clones, the remaining stems may appear to be genetically distinct clones.…”
Section: Discussionmentioning
confidence: 99%
“…First, the demography of seaweeds, like that of many clonal taxa, depends more on size than age (Caswell 1985;Collado-Vides 2002), enabling variants to readily accumulate in genetic individuals (genets) that avoid senescence by continually generating new modules. Second, like ferns and fern allies, growth in seaweeds frequently results from the serial mitotic divisions of single-celled apical meristems, ensuring the spread of acquired mutations to all derived modules (Klekowski 2003). Virtually any diploid cell-including those of mutant lineages-may potentially yield gametes (Santelices 1990), whereas variants arising in the multicellular meristems of seed plants do not necessarily pass to subsequent modules, and only those affecting floral primordia are sexually transmissible (Whitham and Slobodchickoff 1981).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, plants cannot escape environmental hazards, such as drought, high salinity, or heavy metals in the soil, all of which cause oxidative stress, DNA damage, and, consequently, mutations (10). Particularly in the shoot meristem, somatic mutations within the stem cell population can become fixed, contribute to the germline, and reduce reproductive fitness (11). Therefore, protection from DNA damage should be especially important within plant stem cell niches.…”
mentioning
confidence: 99%